Outcome of patients presenting 6 to 12 hours after isolated vascular trauma in a tertiary care hospital of Pakistan - Ammar , Ahmed Siddique; Naqi, Syed Asghar; Liaquat, Affifa; Janjua, Azwa Munim; Syed, Adeena; Ali, Syeda Ifrah (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the outcome of vascular injuries in patients presenting 6-12 hours after isolated vascular trauma. Method: The analytical cross-sectional study was conducted at East Surgical Ward of Mayo Hospital, Lahore, Pakistan, from July 1, 2020, to June 30, 2022 and comprised consecutive patients of either gender aged >13 years with isolated vascular trauma presenting 6-12 hours after vascular injury. Operative procedures included ligation, end-to-end repair and reverse venous graft of the injured vessels. Outcomes, including cause of amputation and mortality, were noted. Data was analysed using SPSS 26. Results: Of the 82 patients, 61(74.03%) were males and 21(25.06%) were females. The overall mean age was 33±5.41 years. Femoral artery was damaged more 54(65.85%) compared to brachial artery 28(34.14%) in all modes of injuries. Ligation of vessel was done in 35(42.68%) cases. Mortality was the outcome in 15(18.29%) patients, amputation in 29(35.36%) and discharge after successful vascular repair 38(46.34%). Conclusion: Ligation of the femoral or brachial artery was found to be a safe and lifesaving procedure in patients presenting 6-12 hours after isolated vascular trauma to the emergency department in a tertiary care setting. Key Words Vascular system injuries, Amputation, Surgical, Brachial artery, Femoral artery.